DOI: 10.23860/diss-jamwal-rohitash-2018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Alcoholic Fatty Liver Disease (Nafld) on Hepatic Drug Metabolism Enzymes in Human

Abstract: Significant changes in dietary habits have led to a rampant increase in metabolic disorders. Non-alcoholic fatty liver disease (NAFLD) is one such disorder characterized by the excess buildup of fat in hepatocytes of people who drink little or no alcohol. If not managed, NAFL (simple steatosis) progress into nonalcoholic steatohepatitis (NASH) and further deteriorate to cirrhosis leading to severe illness or even death. Drug disposition proteins (enzymes and transporters) in liver control the systemic exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 117 publications
(144 reference statements)
0
3
0
Order By: Relevance
“… 36 Protein levels of hepatic CYP2E1 in patients with NAFLD did not seem to increase substantially compared with a BMI‐matched non‐NAFLD control group. 39 The apparent clearance (clearance/oral bioavailability) of chlorzoxazone, a selective CYP2E1 probe, in non‐T2DM NASH patients was only slightly higher (24% difference in mean values) than that of healthy individuals with a similar BMI range. 60 This was in concordance with the formation of 6‐hydroxychlorzoxazone (catalyzed by CYP2E1), which was not altered in obese patients with NAFL, but was higher in morbidly obese NASH patients compared with a non‐NAFLD obese cohort.…”
Section: Impact Of Nafld On Clinical Pharmacokineticsmentioning
confidence: 96%
See 2 more Smart Citations
“… 36 Protein levels of hepatic CYP2E1 in patients with NAFLD did not seem to increase substantially compared with a BMI‐matched non‐NAFLD control group. 39 The apparent clearance (clearance/oral bioavailability) of chlorzoxazone, a selective CYP2E1 probe, in non‐T2DM NASH patients was only slightly higher (24% difference in mean values) than that of healthy individuals with a similar BMI range. 60 This was in concordance with the formation of 6‐hydroxychlorzoxazone (catalyzed by CYP2E1), which was not altered in obese patients with NAFL, but was higher in morbidly obese NASH patients compared with a non‐NAFLD obese cohort.…”
Section: Impact Of Nafld On Clinical Pharmacokineticsmentioning
confidence: 96%
“…65,66 This is in line with nonsignificant changes in protein levels of CYP2C9 (involved in warfarin metabolism) and CYP4F2 (responsible for catabolism of vitamin K and associated with interindividual variability in warfarin response) in patients with non-cirrhotic NAFLD compared with non-NAFLD individuals with similar BMI. 39 Despite observing no change in warfarin daily dose relative to the control group, Zhang et al 66 reported a lower international normalized ratio to warfarin dose ratio in NAFLD (cirrhosis status not reported), suggesting potential NAFLDmediated alterations in vitamin K regulation or other pharmacodynamic factors that may impact warfarin response. It should be noted, however, that this study did not control for pharmacogenetic factors involved in warfarin response.…”
Section: Impact Of Nafld On Clinical Pharmacokineticsmentioning
confidence: 98%
See 1 more Smart Citation